2003
DOI: 10.1038/nm930
|View full text |Cite
|
Sign up to set email alerts
|

β1-adrenergic receptor polymorphisms confer differential function and predisposition to heart failure

Abstract: Catecholamines stimulate cardiac contractility through beta(1)-adrenergic receptors (beta(1)-ARs), which in humans are polymorphic at amino acid residue 389 (Arg/Gly). We used cardiac-targeted transgenesis in a mouse model to delineate mechanisms accounting for the association of Arg389 with human heart failure phenotypes. Hearts from young Arg389 mice had enhanced receptor function and contractility compared with Gly389 hearts. Older Arg389 mice displayed a phenotypic switch, with decreased beta-agonist signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
172
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(183 citation statements)
references
References 26 publications
7
172
2
2
Order By: Relevance
“…In addition, Liu et al (2003) also reported greater metoprolol-evoked bradycardia in homozygous Arg389 than homozygous Gly389. Furthermore, homozygous Arg389 patients with end-stage heart failure, but not homozygous Gly389 patients, showed significant improvement of the left ventricular ejection fraction when treated with the b-blocker carvedilol (Perez et al, 2003). The more marked effect of atenolol and metoprolol, as well as the selective effect of carvedilol, could be due to higher affinity of these b-blockers for Arg389-b 1 -adrenoceptors than Gly389-b 1 -adrenoceptors.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, Liu et al (2003) also reported greater metoprolol-evoked bradycardia in homozygous Arg389 than homozygous Gly389. Furthermore, homozygous Arg389 patients with end-stage heart failure, but not homozygous Gly389 patients, showed significant improvement of the left ventricular ejection fraction when treated with the b-blocker carvedilol (Perez et al, 2003). The more marked effect of atenolol and metoprolol, as well as the selective effect of carvedilol, could be due to higher affinity of these b-blockers for Arg389-b 1 -adrenoceptors than Gly389-b 1 -adrenoceptors.…”
Section: Introductionmentioning
confidence: 91%
“…Table 2 Potencies of (À)-isoprenaline and (À)-CGP12177 and antagonism by (À)-propranolol (200 nM) on recombinant Arg389-b 1 -adrenoceptors and Gly389-b 1 -adrenoceptors b-adrenoceptor blockade with carvedilol (Perez et al, 2003). Furthermore, b 1 -adrenoceptor blockade with atenolol (Sofowora et al, 2003) and metoprolol (Liu et al, 2003) appears to reduce systolic pressure in Arg389 healthy volunteers but not in Gly389 volunteers.…”
Section: The Affinity Of B-blockers Is Conserved Across the Arg389glymentioning
confidence: 99%
“…46 The association of this allele with antihypertensive response to beta-blocker therapy is less straight forward. Several small studies have revealed positive results with the C allele corresponding to an improved response to beta-blockade as defined by reduction in BP or heart failure endpoints [47][48][49][50][51] . Studies have also illustrated contradictory results where the G allele is associated with more favorable rate control with verapamil and multiple beta-blockers 52 .…”
Section: Candidate Pharmacodynamic Polymorphisms Of Adrenergic Responsementioning
confidence: 99%
“…In vitro studies have provided evidence for their functional basis, [1][2][3] and these polymorphisms have been implicated in differential response to b 1 -and b 2 -AR antagonists and agonists in numerous studies. Specifically, studies have shown that b 1 -AR genotype is a significant predictor of blood pressure and ejection fraction responses to b-blockers, [4][5][6][7][8] and responses to b 2 agonists have been associated with b 2 -AR polymorphisms. 9,10 Dobutamine is a potent synthetic intravenous inotrope that is principally an agonist at b 1 -AR with mild stimulatory effects at b 2 -AR and a 1 -AR.…”
Section: Introductionmentioning
confidence: 99%